Proof-of-Concept on Misalignment Compensation for 5.8-GHz-Band Reflectarray Antennas by Varactor Diodes - Keisuke Omoto; Takashi Tomura; Hiraku Sakamoto (IEEE Access, 2021)
Membrane reflectarray antennas with flexible support structures realize low weight and low stowage volume. However, deformation of the reflectarray membrane generally degrades antenna gain. We propose electrical misalignment compensation for 5.8-GHz-band reflectarray antennas by varactor diodes. Active reflection elements are composed of a square patch with the varactor diodes and parameters are characterized in a waveguide. The results of the simulated and measured reflection characteristics agree because of the accurate numerical modelling of the varactor diode. A reflectarray with a stepped structure for misalignment compensation is designed and characterized. The stepped misalignment degrades the antenna gain because the phase distribution is disturbed. Adjusting the reflection phase of the deformed elements compensates the disturbed phase distribution and improves the antenna gain. The gain improvement is confirmed by both simulations and measurements of the antenna gain.